Incidencia de las tasas de interés activas bancarias sobre la distribución de créditos a emprendimientos en Guayaquil - De León Hurtado, Dagmar Mercedes (2025)
The present research called Incidence of bank lending interest rates on the distribution of credits to ventures in Guayaquil; It was carried out with the objective of establishing the relationship that exists between interest rates and loans granted to entrepreneurs, for which a mixed type research methodology was applied, with the development of quantitative tools such as the survey and qualitative tools such as the documentary review, with a descriptive, explanatory and correlational scope (Pearson's correlation coefficient). The result was that there is a negative or inverse correlation between the information taken from interest rates and the amount assigned at the level of credits placed. That is, as interest rates decrease, the reaction of the placement of obligations in ventures increases, a criterion that directly verifies that the financial cost is linked directly and inversely to the contracting of loans by the contracting parties, which is why it was recommended to promote policies to facilitate access to credit for entrepreneurs, offering more accessible interest rates, providing financial education programs for entrepreneurs, and creating strategies to reduce the financial costs of bank loans.